Dual DNA Transfection Using 1,6-Hexanedithiol-Conjugated Maleimide-Functionalized PU-PEI600 For Gene Correction in a Patient iPSC-Derived Fabry Cardiomyopathy Model - Chien, Chian-Shiu; Chien, Yueh; Lin, Yi-Ying; Tsai, Ping-Hsing; Chou, Shih-Jie; Yarmishyn, Aliaksandr A.; Rastegari, Elham; Wang, Ting-Xian; Leu, Hsin-Bang; Yang, Yi-Ping; Wang, Mong-Lien; Jheng, Ying-Chun; et al. (Frontiers in Cell and Developmental Biology, 2021)
Non-viral gene delivery holds promises for treating inherited diseases. However, the limited cloning capacity of plasmids may hinder the co-delivery of distinct genes to the transfected cells. Previously, the conjugation of maleimide-functionalized polyurethane grafted with small molecular weight polyethylenimine (PU-PEI600-Mal) using 1,6-hexanedithiol (HDT) could promote the co-delivery and extensive co-expression of two different plasmids in target cells. Herein, we designed HDT-conjugated PU-PEI600-Mal for the simultaneous delivery of CRISPR/Cas9 components to achieve efficient gene correction in the induced pluripotent stem cell (iPSC)-derived model of Fabry cardiomyopathy (FC) harboring GLA IVS4 + 919 G > A mutation. This FC in vitro model recapitulated several clinical FC features, including cardiomyocyte hypertrophy and lysosomal globotriaosylceramide (Gb3) deposition. As evidenced by the expression of two reporter genes, GFP and mCherry, the addition of HDT conjugated two distinct PU-PEI600-Mal/DNA complexes and promoted the co-delivery of sgRNA/Cas9 and homology-directed repair DNA template into target cells to achieve an effective gene correction of IVS4 + 919 G > A mutation. PU-PEI600-Mal/DNA with or without HDT-mediated conjugation consistently showed neither the cytotoxicity nor an adverse effect on cardiac induction of transfected FC-iPSCs. After the gene correction and cardiac induction, disease features, including cardiomyocyte hypertrophy, the mis-regulated gene expressions, and Gb3 deposition, were remarkably rescued in the FC-iPSC-differentiated cardiomyocytes. Collectively, HDT-conjugated PU-PEI600-Mal-mediated dual DNA transfection system can be an ideal approach to improve the concurrent transfection of non-viral-based gene editing system in inherited diseases with specific mutations.